Biocides united - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A good collection of natural products traditionally used for crop protection can be found in the online database of Natural and Traditional Pesticidal (NTRAP) materials in eastern Africa. For instance, Phytolacca dodecandra known, as uwoko in...